ChemInform Abstract: Synthesis and Crystal Chemistry of the Fast Li‐Ion Conductor Li7La3Zr2O12 Doped with Fe. Issue 37 (22nd August 2013) - Rettenwander, Daniel; Geiger, Charles A.; Amthauer, Georg
Abstract The title compound is synthesized by sintering of Li2CO3, La2O3, ZrO2, and Fe2O3 in air (Pt crucible, 1100 °C, 17 h).